2012
DOI: 10.1021/bm300651q
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Ligament–Bone Interface Regeneration Using a Trilineage Coculture System on a Hybrid Silk Scaffold

Abstract: The ligament-bone interface is a complex structure that comprises ligament, fibrocartilage, and bone. We hypothesize that mesenchymal stem cells cocultured in between ligament and bone cells, on a hybrid silk scaffold with sections suitable for each cell type, would differentiate into fibrocartilage. The section of scaffold for osteoblast seeding was coated with hydroxyapatite. A trilineage coculture system (osteoblasts-BMSCs-fibroblasts) on a hybrid silk scaffold was established. RT-PCR results and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…Given the importance of heterotypic cell communication for enthesis regeneration, it has been hypothesized that cellular cross-talk may be able to promote MSC differentiation via intercellular signals and paracrine factors [46]. To analyze the effect of heterotypic cell interaction on BMSCs differentiation, He et al Accordingly, calcium deposition was found only when BMSCs were co-cultured with osteoblasts, but not with fibroblasts [111]. These findings suggest that heterotypic cellular communication plays a key role in influencing MSC fate and demonstrates the feasibility of co-culture strategies for the generation of a fibrocartilage-like tissue [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Given the importance of heterotypic cell communication for enthesis regeneration, it has been hypothesized that cellular cross-talk may be able to promote MSC differentiation via intercellular signals and paracrine factors [46]. To analyze the effect of heterotypic cell interaction on BMSCs differentiation, He et al Accordingly, calcium deposition was found only when BMSCs were co-cultured with osteoblasts, but not with fibroblasts [111]. These findings suggest that heterotypic cellular communication plays a key role in influencing MSC fate and demonstrates the feasibility of co-culture strategies for the generation of a fibrocartilage-like tissue [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[117] Superior mechanical properties and biocompatible characteristics have made silk a promising material for interface regeneration strategies. [118,119] The presence of osteoblasts and fibroblasts in the adjacent regions, allowed BMSCs to differentiate into both the lineages, thereby giving rise to a transitional region.…”
Section: Nanoengineered Bone-ligament Interfacementioning
confidence: 99%
“…This hybrid silk scaffold supported a tri-lineage environment and the researchers aimed to construct grafts for ACL treatments. [117] Another nontraditional approach to bone-ligament regeneration involved fabrication of two-and three-dimensional electrospun scaffolds. [120] PCL and PLGA were respectively chosen for the aligned and random portions of the scaffold and the transition region contained both materials (Figure 8a,b).…”
Section: Nanoengineered Bone-ligament Interfacementioning
confidence: 99%
“…As a result, the ability to withstand mechanical loads is reduced, thereby leading to re-injuries. 2,8 Therefore, regenerating the enthesis is a common clinical problem, and current approaches for engineering tissue using cells (mesenchymal stem cells (MSCs)) 9,10 and scaffolds (hybrid silk, 9 nanofibre, 11 ) have achieved only limited success in this area. 12 …”
Section: Introductionmentioning
confidence: 99%